Semantic Analysis of 'Song For The Last Act' by Louise Bogan - Sumarni, Sumarni (Action Research Literate, 2025)
This study conducts a semantic analysis of Louise Bogan's poem "Song for the Last Act," focusing on two primary research questions: (1) How is the meaning of death expressed in Bogan's poem? and (2) How do social and cultural contexts influence the interpretation of this poem? The analysis reveals that Bogan employs rich imagery and metaphorical language to convey the inevitability and complexity of death, reflecting both personal and universal themes. Additionally, the socio-cultural backdrop of Bogan's time, particularly the early 20th century's shifting attitudes towards mortality and existentialism, significantly shapes the poem's interpretation. Utilizing a qualitative research methodology, this study draws on literary theory and contextual analysis to explore these dimensions in depth. The findings underscore the intricate relationship between text and context, illustrating how Bogan's work resonates with contemporary readers while remaining rooted in its historical milieu.